Sketches New and Old, Part 7. - Twain, Mark, 1835-1910 (Salt Lake City, UT : Project Gutenberg, 2004)
"Sketches New and Old, Part 7." by Mark Twain is a section from a collection of short stories published in 1875. This segment features tales ranging from humorous observations to satirical commentary, including pieces about political life, frontier journalism, and peculiar social customs. The collection blends Twain's signature wit with his sharp eye for human absurdity. Nearly all stories are fictional, showcasing the author's versatile storytelling across diverse American settings and situations. (This is an automatically generated summary.)
First interview with Artemus Ward -- Cannibalism in the cars -- The killing of Julius Caesar "localized" -- The widow's protest -- The scriptural panoramist -- Curing a cold -- A curious pleasure excursion -- Running for governor -- A mysterious visit.
Wikipedia page about this book: https://en.wikipedia.org/wiki/Sketches_New_and_Old
Release date is 2004-06-27
Produced by David Widger
Keywords: Humorous stories, American; United States -- Social life and customs -- Fiction